Maize tillering, leaf area, and grain productivity underSdifferent spatialarrangement Perfilhamento, área foliar e produtividade do milho sob diferentes arranjos espaciais - Schweitzer C.* (2011)
The objective of this work was to evaluate the effect of plant spatial arrangement on maize tillering, leaf area, and grain productivity. The experiments were carried out in the spring/summer of the 2007/2008 and 2008/2009 growing seasons. Treatments consisted of four plant densities (three, five, seven, and nine plants per square meter) and three row spacings (0.4, 0.7, and 1.0 m). The leaf area index (LAI) and grain yield of hybrid P30F53 were assessed, as well as the tiller contribution to these characters. In 2007/2008, there was no water deficit, LAI values were higher than 7, and tillers contributed with 65% of total LAI at the lowest plant density. In this year, grain yield average (13.7 Mg ha -1) was not affected by treatments, and tillers contributed with 44% of total yield at the density of three plants per square meter. In 2008/2009, there was water deficit before flowering and during grain filling, which decreased tillering and tiller contribution to LAI. Grain yield in this year increased from 9.7 to 11.7 Mg ha -1 with increasing plant densities, but tiller contribution to grain yield was lower. Tillering increases phenotypic stability of grain productivity to variations in plant spatial arrangement.